PERSPEKTIF HUKUM EKONOMI TERHADAP STRATEGI INDUSTRIALISASI - Setiobudi, F. Rahardjo (Jurnal Cakrawala Hukum, 2014)
Government policy in industrial sector was considered ‘fail’ in industrialization in Indonesia because itignored innovation culture and resource potency.Both were based on thehuman problem as the main step of life.The experiences in many countries in which their process of industrialization always succeeded proved thatthey always gave priority to human as the source and also the goal of the industrial creation itself. On the otherside,the law function as the medium of industrialization in Indonesia could not grow innovation culture eitherbecauseit merely served economy activities of industrialization. The idea proposed to improve this case was theuse of the two pillars, namely innovation culture and social structure, as the industrialization planningfoundation and the law function or use in economic development in Indonesia.